1999
DOI: 10.1007/s004420050844
|View full text |Cite
|
Sign up to set email alerts
|

Response of a root hemiparasite to elevated CO 2 depends on host type and soil nutrients

Abstract: Although elevated CO may affect various forms of ecological interactions, the effect of elevated CO on interactions between parasitic plants and their hosts has received little attention. We examined the effect of elevated CO (590 μl l) at two nutrient (NPK) levels on the interactions of the facultative root hemiparasite Rhinanthus alectorolophus with two of its hosts, the grass Lolium perenne and the legume Medicago sativa. To study possible effects on parasite mediation of competition between hosts, the para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 32 publications
4
62
6
Order By: Relevance
“…Bardgett et al (2006) found no interactions between R. minor and soil fertility or manure application on aboveground biomass in a mesocosm experiment, but R. minor increased species diversity in lownutrient soil. The results of two-pot culture experiments suggest that the eVect of a parasite was greater in nutrientpoor soils (Matthies and Egli 1999;Davies and Graves 2000), although the latter study did not report results for the interaction, while Cameron et al (2005) showed that R. minor had a larger eVect on competitive abilities of the grass Poa pratensis under high-nutrient levels. Together, these studies, and those of Cameron et al (2009), suggest that eVects of hemiparasites on communities are not straight-forward responses to resource supply in many systems.…”
Section: (B)mentioning
confidence: 81%
See 1 more Smart Citation
“…Bardgett et al (2006) found no interactions between R. minor and soil fertility or manure application on aboveground biomass in a mesocosm experiment, but R. minor increased species diversity in lownutrient soil. The results of two-pot culture experiments suggest that the eVect of a parasite was greater in nutrientpoor soils (Matthies and Egli 1999;Davies and Graves 2000), although the latter study did not report results for the interaction, while Cameron et al (2005) showed that R. minor had a larger eVect on competitive abilities of the grass Poa pratensis under high-nutrient levels. Together, these studies, and those of Cameron et al (2009), suggest that eVects of hemiparasites on communities are not straight-forward responses to resource supply in many systems.…”
Section: (B)mentioning
confidence: 81%
“…Pot culture experiments indicate that the eVect of a parasite on an individual host is greater under low-nutrient conditions (Gibson and Watkinson 1991;Matthies and Egli 1999; but see Cameron et al 2005), and mesocosm experiments indicate that some community-level eVects decline with soil fertility (Bardgett et al 2006). For parasitism to depress community productivity, the parasite-induced reduction in the growth of hosts must exceed the contribution of the parasite mass (Hautier et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…In the same way, since parasitic plants selectively depress the biomass of preferred host taxa, plant parasitism can alter the competitive balance between preferred and nonpreferred hosts (Gibson and Watkinson 1991;Matthies 1996;Callaway and Pennings 1998; but see Matthies and Egli 1999). As a result of this indirect effect, the species composition of the non-parasitic vegetation may differ between communities with and without parasitic plants (Gibson and Watkinson 1992;Pennings and Callaway 1996;Joshi et al 2000).…”
Section: Impacts On Communitiesmentioning
confidence: 96%
“…Although hemiparasitic plants also reduce the biomass of their host community, this reduction can occasionally be compensated for, or even exceeded by, the production of the parasite (Marvier 1996;Joshi et al 2000). Thus, the net effect of a hemiparasite on total plant community biomass can be negative, neutral or positive, although negative effects are most typical (Mizianty 1975;Matthies 1995Matthies , 1996Matthies , 1998Marvier 1998b;Matthies and Egli 1999;Joshi et al 2000).…”
Section: Impacts On Communitiesmentioning
confidence: 97%
See 1 more Smart Citation